Endogenous contrast MRI of cardiac fibrosis: Beyond late gadolinium enhancement. Issue 5 (5th August 2014) - van Oorschot, Joep W.M.; Gho, Johannes M.I.H.; van Hout, Gerardus P.J.; Froeling, Martijn; Jansen of Lorkeers, Sanne J.; Hoefer, Imo E.; Doevendans, Pieter A.; Luijten, Peter R.; Chamuleau, Steven A.J.; Zwanenburg, Jaco J.M.
<x xml:space="preserve">Abstract</x> The aim of this review is to provide an overview of detection of cardiac fibrosis with MRI using current standards and novel endogenous MRI techniques. Assessment of cardiac fibrosis is important for diagnosis, prediction of prognosis and follow‐up after therapy. During the past years, progress has been made in fibrosis detection using MRI. Cardiac infarct size can be assessed noninvasively with late gadolinium enhancement. Several methods for fibrosis detection using endogenous contrast have been developed, such as native T1‐mapping, T1ρ‐mapping, Magnetization transfer imaging, and T2*‐mapping. Each of these methods will be described, providing the basic methodology, showing potential applications from applied studies, and discussing the potential and challenges or pitfalls. We will also identify future steps and developments that are needed for bringing these methods to the clinical practice. J. Magn. Reson. Imaging 2015;41:1181–1189. © 2014 Wiley Periodicals, Inc.